2022
DOI: 10.3390/ijerph19159759
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Stress Disorder, Major Depressive Disorder, and Wildfires: A Fifth-Year Postdisaster Evaluation among Residents of Fort McMurray

Abstract: Background: Over 90,000 residents had to be evacuated from Fort McMurray (FMM), Alberta, Canada due to the wildfire that engulfed the city in May 2016. Overall, about 2400 homes or 10% of the housing stock in Fort McMurray were destroyed. The fire consumed about 200,000 hectors of forest, reaching into Saskatchewan. During major disasters, communities’ infrastructure is disrupted, and psychological, economic, and environmental effects are felt for years afterwards. Objective: Five years after the wildfire disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 81 publications
7
27
0
Order By: Relevance
“…A score ≥ 44 denotes likely PTSD, while ≤44 shows unlikely PTSD. The PCL-C demonstrates high internal consistency (Cronbach's = 0.94) and acceptable reliability and convergent validity [48].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…A score ≥ 44 denotes likely PTSD, while ≤44 shows unlikely PTSD. The PCL-C demonstrates high internal consistency (Cronbach's = 0.94) and acceptable reliability and convergent validity [48].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…In this cohort study of large California wildfires from 2001 to 2018, the analysis demonstrated a significant association between psychotropic medication fills and wildfires consistent with previous literature describing mental health risk associated with wildfires, but on a broader spatial and timescale using administrative prescription data. 3,4,[7][8][9]13,28 These findings warrant further examination of mental health effects related to wildfires, including exploration of exposure pathways and mechanisms for mental health effects, incident diagnoses compared with exacerbation of preexisting mental health conditions, and identification of mental health needs in communities and populations disproportionately affected by wildfires. Further investigation on mental health prescription medications is needed, particularly focusing on populations with limited or no access to mental health services, so that appropriate public health measures can be implemented with an emphasis on addressing medication needs of affected populations.…”
Section: Discussionmentioning
confidence: 98%
“…11,12 Furthermore, published studies have identified associations between wildfire and impaired mental health including anxiety, depression, and PTSD, but these studies have relied primarily on qualitative methods or focused on a particular wildfire or season; and, to our knowledge, none have used prescriptions of psychotropic medications as a proxy for mental health burden nor evaluated across wildfire seasons. 3,4,[7][8][9]13 We hypothesized that the presence of large wildfires in California, especially near population centers, would be associated with exacerbations of underlying mental health conditions. Toward this end, our objective for this study was to analyze associations between large wildfires in California and prescription rates of various psychotropic medication categories as a proxy indicator of public mental health burden.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations